2020
DOI: 10.1136/neurintsurg-2020-016790
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of distal aneurysm treatment with flow diversion in the M2 segment of the middle cerebral artery and beyond

Abstract: BackgroundIndications for flow diversion stent (FDS) treatment are expanding. However, there is still a lack of evidence for the long-term outcome in distally located aneurysms in the M2 segment of the middle cerebral artery (MCA) and beyond.MethodsConsecutive subjects (from June 2013 to August 2020) with MCA aneurysms in the M2 segment or beyond treated with FDS were reviewed retrospectively. The primary endpoints for clinical safety were the absence of mortality, stroke event, re-rupture of the aneurysm, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
15
1
1
Order By: Relevance
“…The densely braided mesh of a flow diversion stent delivered at the aneurysm base decreases the blood flow into the aneurysm and induces thrombus formation within the aneurysm sac while maintaining adequate blood flow through the parent artery and the covered vessel branches (5). The development of smaller flow diverters like Flow Re-Direction Endoluminal Device Jr (FRED Jr; MicroVention, Tustin, California), which can be delivered into small-caliber (<3 mm diameter) vessels, enabled the expansion of indications for flow diversion stent treatment in smaller parent vessels (2,6). However, there is only a limited number of studies evaluating flow diverter devices specifically developed for smaller arteries (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…The densely braided mesh of a flow diversion stent delivered at the aneurysm base decreases the blood flow into the aneurysm and induces thrombus formation within the aneurysm sac while maintaining adequate blood flow through the parent artery and the covered vessel branches (5). The development of smaller flow diverters like Flow Re-Direction Endoluminal Device Jr (FRED Jr; MicroVention, Tustin, California), which can be delivered into small-caliber (<3 mm diameter) vessels, enabled the expansion of indications for flow diversion stent treatment in smaller parent vessels (2,6). However, there is only a limited number of studies evaluating flow diverter devices specifically developed for smaller arteries (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, flow diversion devices have been reported as an alternative endovascular treatment for complex MCA aneurysms. Cimflova et al (28) reported that the complete/near-complete occlusion rate was 70% in consecutive subjects with 23 MCA aneurysms. Potentially severe periprocedural or postprocedural events occurred in 17.4% of the patients and severe complications (intraparenchymal hemorrhage and rerupture of the aneurysm) occurred in half of those patients (8.7%), which was consistent with previous studies (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to that, Salem et al found that MCA-bifurcation aneurysms are treatable with much lower complication rates, the outcomes of their study being comparable to other, well consented FD locations [ 45 ]. Cimflova and coworkers contributed their experience with less than 9% significant complications after FD implantation in the MCA distal to the M1 segment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%